Financialisation, institutions and financing constraints in developing countries. (23rd May 2019) - Mertzanis, Charilaos
Abstract: The paper uses a consistent firm-level data from the World Banks Enterprise Surveys to explore the impact of financialisation in the economy on firms' access to finance in 138 developing countries. Access to finance reflects survey-based firms' perceptions of external financing constraints. Financialisation is proxied by consistent cross-country measures of financial depth. These proxies capture separately the role of bank-based versus market-based financing. Firm-, sector- and country-level information is jointly used for the analysis. Firm-specific characteristics and economic and non-economic national factors are included as controls. The results show that the proxies of financialisation are broadly robust predictors of financing constraints of firms in developing countries. However, the magnitude of the financialisation effect varies between bank-based and market-based channels of financing as well as between low- and high-income countries, and it is influenced by social, institutional and religious factors.